The Effects of Modified and Normal Taper on Mood States, Cortisol Level and 20km Time Trial Performance Among Elite Junior Cyclist - ASMADI ISHAK,; HAIRUL ANUAR HASHIM,; OLEKSANDR KRASILSHCHIKOV, (International Journal of Pharma and Bio Sciences, 2018)
Strategies that maximize positive mood states and minimize negative mood states may contribute to athletes’ performance. These performance-maximizing strategies include Taper. This study compared the effects of a 2-week modified exponential taper on mood state and cycling time-trial performance among elite junior cyclists (N = 27; mean age = 16.95 years, SD = 0.8). They were assigned to a modified exponential; taper, a normal exponential taper, or a control group. Both the modified and normal exponential taper groups had more positive mood states than the control group; however, no differences were found between the modified and normal taper groups. Moreover, both taper groups had lower post-taper cortisol levels and faster time-trial performance than the control group. Significant relationships were also found between 20-km time-trial performance and vigor (r = - 0.81), fatigue (r = 0.66), and cortisol (r = 0.73). No other significant relationships were found. In summary, the modified and normal taper programs were equally effective in regulating mood state and improving cycling performance.